Prevention of haematomas after auricular injuries - R. J. Martin,* V. M. Carey, R. F. Philbert, J. B. Carter (Blackwell Synergy, 2000)
Many of the injuries treated by oral and maxillofacial surgeons are facial lacerations, Lacerations and avulsive injuries of the auricle are rare, but when they do occur, the repair coupled with postoperative management presents a challenge. A haematoma resulting from vascular injury and subsequent accumulation of subperichondral fluid is one of the serious post-traumatic complications. If these haematomas are not evacuated, the result may be a deformity of the ear that may require operation.